Bergenin ameliorates chemotherapy-induced neuropathic pain in rats by modulating TRPA1/TRPV1/NR2B signalling - Akhilesh; Chouhan D.; Ummadisetty O.; Verma N.; Tiwari V. (My University, 2025)
Chemotherapy-induced neuropathic pain (CINP) is one of the most prominent and incapacitating complication associated with chemotherapeutic regimens. The exact mechanisms underlying CINP are not fully understood yet, which hampers the development of effective therapeutics. The current study has been designed to investigate the effect of bergenin on CINP and dissect the underlying cellular and molecular mechanisms. Behavioural responsiveness assays were conducted in rats before and after CINP induction and at different time points post-bergenin treatment. We also measured alterations in tight junction proteins, pro-inflammatory cytokines, microglia activity, transient receptor potential (TRP) channels (TRPV1, TRPA1 and TRPM8) and N-methyl-D-aspartate receptor subtype 2 (NR2B) in dorsal root ganglion (DRG) and spinal tissues of neuropathic rats. Bergenin treatment leads to a significant and dose-dependent reduction in evoked and spontaneous ongoing pain without causing central side effects in neuropathic rats. Furthermore, treatment with bergenin and gabapentin did not affect the baseline pain threshold in healthy, non-chemotherapy-treated rats, as evaluated through tail-flick and tail-clip assays. Chemotherapy administration leads to a significant activation of TRP channels, concurrent with microglial activation, disruption of spinal cord tight junction proteins, and subsequent infiltration of pro-inflammatory cytokines, as well as NR2B activation. Notably, bergenin treatment effectively reversed all of these alterations, with the exception of TRPM8, in both the DRG and spinal cord of neuropathic rats. Findings from the present study suggests that bergenin mitigates neuropathic pain by modulating the TRPA1/TRPV1/NR2B signalling and presents a promising therapeutic avenue for the treatment of chemotherapy-induced neuropathic pain. © 2023 Elsevier B.V.